PENGEMBANGAN PANDUAN LAYANAN PEMANTAPAN KARIER UNTUK MENINGKATKAN EFIKASI DIRI PESERTA DIDIK MADRASAH ALIYAH - Maryam, Rohana; Kamalia, Arini Nur Ihsanil; Rizal, Agus (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2023)
This study aims to develop career guidance teaching panduanes for students in an appropriate manner and to improve understanding and increase self- efficacy effectively. The research method used is research and development with reference to Borg Gall's research steps. The subject of this study was guidance and counseling teacher MA Gani Tirtoasri, and small group trials were conducted on two people. The results of the data in this study were descriptive, qualitative, and quantitative (RnD). The data collection process involves the results of the analysis in the form of a panduane or book rating scale, which can show the results of the product feasibility level. The results of this study show that the monitoring panduane of the career of learners in the digital age is worthy to be used as a panduane in guidance and counseling services. The results are obtained from the results of the validation assessment of the media expert in this case who is the validator is dr. Bakhrudin All Habsy, M.Pd is with a presentation of 86.6% which means good/good, the validation of the expert material in this case that becomes the validator is Wisnu Kurniawan, Pd this assessment results obtained a presentation of 92.7% with a category of good / good, on a small group trial obtain a presentation 95% which is included in a category very good. The conclusion of this product is that it is good to use. As a suggestion, in order to produce a better product, this development panduane should continue the Borg Gall development phase until the final step.